Mudejarismo and Moorish Revival in Europe
1 online resource.
Keywords: Mudejarismo and Moorish Revival in Europe examines key aspects related to the reception of Ibero-Islamic architecture in medieval Iberia and 19th-century Europe. It challenges prevalent readings of architecture and interiors whose creation was the result of cultural encounters. As Mudéjar and neo-Moorish architecture are closely connected to the Islamic world, concepts of identity, nationalism, religious and ethnic belonging, as well as Orientalism and Islamoscepticism significantly shaped the way in which they have been perceived over time. This volume offers art historical and socio-cultural analysis of selected case studies from Spain to Russia and opens the door to a better understanding of interconnected cultural and artistic phenomena.